Spectral analysis of rotor current of induction motor as indicator of its effectiveness - V. L. Kodkin; A. S. Anikin; A. A. Baldenkov (Омский научный вестник)
The article substantiates the effectiveness of the analysis of rotor currents of asynchronous electric drives with frequency control. It is proposed to use a spectral analysis of these currents, their main harmonics as the most accurate «display» of slip in an induction motor - as a method for assessing the quality of the motor torque generation. Modeling and experiments confirm the proposed theoretical propositions. These experiments demonstrating the operation of the drive at low loads corresponding to a slip of 3%, with a load close to the nominal corresponding slip of 8-10%, convincingly demonstrated that the torque generation algorithm implemented in standard frequency inverters (for example, ATV, Schneider Electric) is not the most effective, at the same time, a constructive solution is proposed that improves the dynamics of the drive by almost half, making it close to the dynamics of permanent magnet motors. This solution will allow the use of asynchronous electric drives in precision technology.